Moody Margaret casts a spell - Simon, Francesca (London : Orion Children's Books, 2012)
Horrid Henry is much better at magic than Moody Margaret - or so he thinks. But when he tries to put Margaret under his spell he's in for a surprise...
Shelving Location Readers Book Section. Fiction Books
Keywords: English - fiction; Early Readers